5f-3+6-7f=

Simple and best practice solution for 5f-3+6-7f= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5f-3+6-7f= equation:


Simplifying
5f + -3 + 6 + -7f = 0

Reorder the terms:
-3 + 6 + 5f + -7f = 0

Combine like terms: -3 + 6 = 3
3 + 5f + -7f = 0

Combine like terms: 5f + -7f = -2f
3 + -2f = 0

Solving
3 + -2f = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2f = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -2f = 0 + -3
-2f = 0 + -3

Combine like terms: 0 + -3 = -3
-2f = -3

Divide each side by '-2'.
f = 1.5

Simplifying
f = 1.5

See similar equations:

| 9x+22=16x-27 | | (-3x)+8=1-(4x) | | 24=-6b-2b | | 64*x*2-8=41 | | 12(6-1/2x)=240 | | f(7pi/6) | | h-15=4 | | 6k-7+5k= | | 8(3b+2)=-30 | | http://opt-prod.s3.amazonaws.com/traject/files/item_attachments/relateds/000/429/917/original/Equation_6.PNG?1463559659 | | -6=-7x+8x | | 7.32=0.05-.18 | | f=7*32 | | 25*x*2+2=3 | | .3=0.300 | | 5n^2+1=126 | | 60+70+h=410 | | 3(8-2x)=60 | | 4(1+-12y)-3y=1 | | x*2-7=29 | | 2z(2z+7)-30=0 | | 6S-s= | | 129-43=12 | | 5.75+4.50(k-5)=26.25 | | 4b-11=1-2(3-b) | | 97=28*8+x | | 1.5*0=x-3 | | 14+16=-5(5x-6) | | 97=28+x*8 | | -a-5-(-5)a= | | bx+6=dx-6 | | 10y-7=25y+2 |

Equations solver categories